FORMATION OF NATIONAL IDENTITY OF FUTURE LAW SPECIAISTS AT THE NATIONAL AVIATION UNIVERSITY (NAU) - Сопілко, Ірина Миколаївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Purpose: the purpose of the scientific article is to find out the concept of the role and significance of national identity and the peculiarities of its formation in the student environment. Methods: general and special scientific methods have been applied to achieve the set purpose. The use of these methods allowed analyzing the periodization of the national identity formation on the example of the history of the Ukrainian nation development and to focus on the peculiarities of the national identity formation on the example of the activity of the Law Institute of NAU. Outcomes: the author states that change is long overdue in the educational sphere regarding the formation of national-patriotic education, which requires a comprehensive approach. The author suggests improving the forms and methods of educational activities in order to form a patriotically minded future law specialist. Discussion: discussion on the main goal of education: whether to give structured fundamental knowledge or to teach how to think freely and learn independently using available opportunities on the basis of the formed patriotically minded Ukrainians.